Transfer of the Long Head Biceps Tendon to Conjoined Tendon in Proximal Humerus Fractures with Cleavage or Comminution at the Bicipital Groove - Momenzadeh, Omid Reza; Mesbahi, Seyed Amirreza; Azimi, Fatemeh Sadat; Mardani-Kivi, Mohsen (Bulletin of emergency & trauma, 2022)
To evaluate the clinical and radiographic findings of long head biceps tendon (LHBT) transfer in traumatic proximal humeral fractures with the biceps groove breakage or comminution.ObjectiveTo evaluate the clinical and radiographic findings of long head biceps tendon (LHBT) transfer in traumatic proximal humeral fractures with the biceps groove breakage or comminution.In this interventional study, subjects surveyed in terms of shoulder function, clinical signs of LHBT tendinitis, radiographic signs of transferred biceps as a possible depressor of the shoulder, and mechanical changes of the scapula. Data were analyzed in SPSS version 21.MethodsIn this interventional study, subjects surveyed in terms of shoulder function, clinical signs of LHBT tendinitis, radiographic signs of transferred biceps as a possible depressor of the shoulder, and mechanical changes of the scapula. Data were analyzed in SPSS version 21.Fifteen patients were included in the case group (tendon transfer to the conjoined tendon), and 10 patients were evaluated in the control group (non-transfer or non-manipulation of the exposed tendon in the fracture callus of biceps groove). The mean age of the study population was 46.56±14.31 years, and the majority of patients (14.56%) were men. The differences between two groups were not significant in terms of the American Society of Shoulder and Elbow Surgeons (ASES) score, University of California at Los Angeles (UCLA) score, and constant shoulder score (CSS) (p=0.535, p=0.419, and p=0.266, respectively). Also, there was no significant differences between the case and control groups regarding the biceps muscle involvement (Popeye sign: p=1.00; tenderness: p=0.477; pain: p=1.00; speed test: p=1.00; Yergason's test: p=1.00).ResultsFifteen patients were included in the case group (tendon transfer to the conjoined tendon), and 10 patients were evaluated in the control group (non-transfer or non-manipulation of the exposed tendon in the fracture callus of biceps groove). The mean age of the study population was 46.56±14.31 years, and the majority of patients (14.56%) were men. The differences between two groups were not significant in terms of the American Society of Shoulder and Elbow Surgeons (ASES) score, University of California at Los Angeles (UCLA) score, and constant shoulder score (CSS) (p=0.535, p=0.419, and p=0.266, respectively). Also, there was no significant differences between the case and control groups regarding the biceps muscle involvement (Popeye sign: p=1.00; tenderness: p=0.477; pain: p=1.00; speed test: p=1.00; Yergason's test: p=1.00).LHBT transfer to the conjoined tendon in proximal humerus fractures with cleavage or comminution at the bicipital groove showed no advantages.ConclusionLHBT transfer to the conjoined tendon in proximal humerus fractures with cleavage or comminution at the bicipital groove showed no advantages.